A community for students.
Here's the question you clicked on:
← 55 members online
 0 viewing
anonymous
 one year ago
A system of equations is given below:
y = 4x − 3
2x + 7y = 41
Which of the following steps could be used to solve by substitution?
2(y = 4x − 3) + 7y = 41 4x − 3 = 2x + 7y 2x + 7(4x − 3) = 41 2(y = 4x − 3)
anonymous
 one year ago
A system of equations is given below: y = 4x − 3 2x + 7y = 41 Which of the following steps could be used to solve by substitution? 2(y = 4x − 3) + 7y = 41 4x − 3 = 2x + 7y 2x + 7(4x − 3) = 41 2(y = 4x − 3)

This Question is Closed

Michele_Laino
 one year ago
Best ResponseYou've already chosen the best response.0from first equation we have y, since: \[\Large y = 4x  3\]

Michele_Laino
 one year ago
Best ResponseYou've already chosen the best response.0now I replace y with 4x3 into the second equation, so I get: \[\Large 2x + 7\left( {4x  3} \right) = 41\]

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0medal me and I will guide you through it

Michele_Laino
 one year ago
Best ResponseYou've already chosen the best response.0hint: dw:1437678290291:dw
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.